PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI RELASI DAN FUNGSI - Nia Herlina Sari; Ika Wahyu Anita; Eneng Maesyaroh (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to examine mathematical critical thinking skills by applying a contextual approach to the material of relations and functions. This research is a classroom action research. The population of this study were students of SMP Negeri 3 Sukatani in Purwakarta Regency with the number of students used as many as 27 students of class VIII B. The data collection technique was through the results of the students' pretest-posttest essay writing based on the main question instrument from the discussion of relations and functions. Based on the results of research and discussion, students' mathematical thinking skills in solving relation and function problems are in the indicator of solving problems on the function value with a percentage of 70% and in solving problems in calculating the number of mappings with a percentage of 75% which is included in the high category. The contributing factor is that students have not been able to think critically in calculating and solving problems in relations and functions, and drawing conclusions.